Generation of transgenic pigs carrying siRNA vector directed against human tissue factor expression. (March 2014) - Ahrens, Hellen; Petersen, Björn; Herrmann, Doris; Lucas‐Hahn, Andrea; Hassel, Petra; Ziegler, Maren; Kues, Wilfried; Niemann, Heiner
<x xml:space="preserve">Abstract</x> Background The acute vascular rejection (AVR) is the major obstacle to successful pig‐to‐primate xenotransplantation. Changes of the endothelium to a procoagulant state which occur after xenotransplantation entail an increased expression of Tissue Factor (TF). This initiates the extrinsic coagulation cascade and results in microvascular thrombosis and rapid loss of organ function. Organs from pigs with a decreased expression of TF could be promising to overcome AVR. Since a homozygous TF knockout had shown to be lethal in mice [1], we decided to use siRNA‐technology to knockdown TF to a basal level. Methods Different siRNAs directed against TF expression were tested in initial studies for their efficacy. A vector coding for the siRNA providing the highest decrease of TF mRNA levels was kindly provided by Dr. Joachim Denner, RKI Berlin. Porcine fetal fibroblasts were co‐transfected with this plasmid and a vector (DsRed, Clontech) which confers neomycin resistance and red fluorescence. After 14 days of selection with 800 μg/ml Geneticin (G418), cells were screened for siRNA expression prior to somatic cell nuclear transfers (SCNTs). Subsequently, the reconstructed embryos were transferred to synchronised recipient sows. Liveborn offspring were analysed by real‐time PCR for TF mRNA quantification. The production of the siRNA was detected via RT‐PCR followed by real‐time PCR. Results An average of 95 embryos per sow was transferred to 28 synchronized recipients. The pregnancy rate was 54%. One sow was sacrificed on day 25 of pregnancy and one fetus (#893/1) was obtained. The candidate siRNA could be detected fetal tissues. Real‐time PCR analysis revealed decreased TF mRNA expression in fibroblasts of fetus #893/1 compared to wild‐type fibroblasts. Therefore, somatic cells from fetus #893/1 was used for recloning. A total of 12 live born piglets could be obtained; five piglets died within few days after delivery. The mRNA levels and production of the siRNA are currently determined. Protein expression analysis by fluorescence cytometry and functionality assessment by coagulation assays are planned for the near future with collaborating laboratories at the Medical School Hannover. Conclusions The AVR is currently the bottleneck in porcine‐to‐primate organ xenotransplantation. Controlling TF‐induced coagulation might provide protective effects for porcine xenografts. Thus, TF knockdown pigs could be critical in producing the ultimate multi‐transgenic pig as organ donor for human patients. References [1] Toomey J, Kratzer K, Lasky N, Stanton J, Broze GJ. Targeted disruption of the murine tissue factor gene results in embryonic lethality. Blood. 1996; 88(5): 1583–1587.